Persepsi Generasi Milenial Terhadap Pekerjaan Pada Sektor Pertanian Di Kecamatan Likupang Selatan Kabupaten Minahasa Utara - Mundung, Dewi Chinta Claudia; Waney, Nordy F.L.; Lumingkewas, Jelly R.D. (AGRI-SOSIOEKONOMI, 2023)
The purpose of the study was to determine the millennial generation's perception of work in the agricultural sector in South Likupang District, North Minahasa Regency. The research was conducted for three months from May to July 2023, located in South Likupang District, North Minahasa Regency. The type of data used in the research is primary data obtained directly through interviews and filling out questionnaires from millennial generation groups. Secondary data were obtained from relevant agencies, namely the South Likupang District Office, the North Minahasa Regency Statistics Agency, research results and literature related to the research conducted. The research population was the millennial generation from farming families in South Likupang District, North Minahasa Regency. Sampling was carried out by proportional sampling, namely sampling that takes into account the elements or categories in the research population. The research population is all children with heads of families with agricultural livelihoods, namely a total of 53 families out of 278 families with heads of families who make a living from the agricultural sector. Data analysis used to see the influence variable used Likert scale. The results showed that the millennial generation's perception of work in the agricultural sector in South Likupang District, North Minahasa Regency on internal factors from the education level indicator was on doubtful criteria, parental support was on very agreeing criteria and peer influence was on very agreeing criteria. External factors in the income indicator are in the criteria strongly agree, the agricultural socialization indicator is in the doubtful criteria and the agricultural innovation indicator is in the criteria strongly agree. Millennial perceptions of employment in the agricultural sector agree that work in the agricultural sector is profitable with a percentage of 73.33 percent.